Binge Drinking in Young Adults Data, Definitions and Determinants. [article]. - Courtney, Kelly E.
Binge drinking is an increasingly important topic in alcohol research, but the field lacks empirical cohesion and definitional precision. The present review findings and viewpoints from the scientific binge-drinking literature. Epidemiological studies quantify the seriousness of alcohol -related problems arising from binge drinking with a growing incidence reported in college-age men over the last 2 years. Experimental studies have found neurocognitive deficits for frontal lobe processing and working memory operations in binge-drinking compared with nonbinge alcohol drinkers. The findings are organized with the goals of providing a useful bunge-drinking definition in the context ofn the empirical results. Theoretical implications are discussed on how binge drinking may alter neurophysiological and neurocognitive function. -- (from the author)